Vaginal delivery following cesarean section: application of a score at admission to the hospital - Vargas Juscamaita, Anny Tatiana (2014)
Objective: To determine if Flamm and Grobman scores are useful  to predict successful vaginal delivery in patients with prior cesarean section. Design: Retrospective comparative study. Setting: Obstetrical Service, Hospital Nacional Cayetano Heredia, Lima, Peru. Participants: Term pregnant women with previous cesarean section. Interventions: Medical records of pregnant women at term who had had previous cesarean section and were admitted to the emergency department in spontaneous labor during the period from January 2010 to December 2011 were reviewed. Demographic and obstetrical data were collected and the Flamm and Grobman scores were applied. Main outcome measures: Usefulness of the scores in the prediction of vaginal delivery in women with previous cesarean section. Results: During the study period, 398 pregnant women at term who had a previous cesarean section were admitted to the emergency department in spontaneous labor. We compared the area under the ROC curve 0.79 (95%IC 0.74–0.82) for the Flamm score and 0.74 (95%IC 0.70-0.79) for the Grobman score, with a statistically significant difference (p=0.03). Comparing both, the Flamm score was better predictor. Conclusions: Both scores were useful to predict a successful vaginal delivery in patients who had previous cesarean section, and the Flamm score was a better predictor.Keywords: Vaginal delivery, cesarean section, Flamm score, Grobman score.